2000
DOI: 10.1351/pac200072101799
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities in solid-state chemistry

Abstract: Abstract:We are largely unable to predict the composition and crystal structure of new extended structure compounds. Yet we find that as materials become more complex in stoichiometry and structure, new, interesting, and perhaps useful, phenomena are encountered. The need for improved experimental and theoretical approaches to seize more rapidly the opportunities provided in this complexity is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 4 publications
1
28
0
Order By: Relevance
“…A 1+x M′ 2-2x M′′ 7-x Se 13 (l ) 2, m ) 2, n ) 2) defines the so-called Sr 4 Bi 6 Se 13 structure type, 33 a very stable architecture that is adopted by many ternary and quaternary systems including K 2 37 and the solid solutions K 2 Bi 8-x Sb x Se 13 for 0 e x e 8. 38 The main characteristic is that the [Bi 6 Se 13 ] 8-part of the structure remains intact while the Sr 2+ positions can be substituted with a variety of similarly sized ions, Ba 2+ , K + , Bi 3+ , Pb 2+ , etc., so long as they maintain electroneutrality.…”
Section: Structural Evolution and Phase Homologies Kanatzidismentioning
confidence: 99%
“…A 1+x M′ 2-2x M′′ 7-x Se 13 (l ) 2, m ) 2, n ) 2) defines the so-called Sr 4 Bi 6 Se 13 structure type, 33 a very stable architecture that is adopted by many ternary and quaternary systems including K 2 37 and the solid solutions K 2 Bi 8-x Sb x Se 13 for 0 e x e 8. 38 The main characteristic is that the [Bi 6 Se 13 ] 8-part of the structure remains intact while the Sr 2+ positions can be substituted with a variety of similarly sized ions, Ba 2+ , K + , Bi 3+ , Pb 2+ , etc., so long as they maintain electroneutrality.…”
Section: Structural Evolution and Phase Homologies Kanatzidismentioning
confidence: 99%
“…ing to a group, including grouping across the periodic table according to the ionic size, oxidation number, polarizibility and presence of lone pairs. Similarity is expressed by a limited number of existing structural types, including preferences for some of them [2,3]. Thermodynamically speaking, it is observed that the number η q of (ordered) phases in phase diagrams is by far not as large than a continuous variation of stoichiometry would anticipate (except solid solutions which are an expression of similarity).…”
Section: Expression Of Similarity Of the Elementsmentioning
confidence: 99%
“…1), we have additionally to take into account stoichiometric variation. From a formal point of view, stoichiometric coefficients in compounds E x1 (1)E x2 (2)...E xn (n) may be continuously varied. Consequently, mathematical reasoning would lead us to a rather pessimistic perspective to support whatever endeavour for exploring the chemical diversity of solid compounds.…”
mentioning
confidence: 99%
“…Nature over geological time scales has synthesized many multicomponent minerals containing typically 3 to 6 elements in different lattice sites and up to a maximum of ten ions in rare cases [10]. Direct synthesis of compound phases with many components other than naturally occurring minerals has been possible, for example in the case of high Tc oxide super conductors as in HgBa 2 Ca 3 Cu 3 O x .…”
Section: Multicomponent Materialsmentioning
confidence: 99%